How bibliographic dataset portrays decreasing number of scientific publication from Indonesia - Nandiyanto, Asep Bayu Dani; Biddinika, Muhammad Kunta; Triawan, Farid (Universitas Pendidikan Indonesia, 2020)
Indonesia faces decreasing in its number during period of 2018-2019 according to SINTA (Indonesian scientific indexing) database. This situation is alarming amid country’s effort to improve its research and development from which the scientific publication has been used as a measure. This article presents a dataset of bibliometric from all Indonesian institutions (424 institutions as of January 2020) indexed by Scopus database. We collected data on documents per year and document type. Different from other datasets, this article presents longitudinal data from 2014-2019, in which during this period dramatic change occurs from steep rise, exponential, and degradation during 2018-2019. We analyzed publication number from leading institutions at different points in time and compared document types (i.e., number of journal article and conference paper, in which both types are the driving force of Indonesia’s growing scientific publication number). Since this dataset covers all country’s institutions, it is potential for reuse by policy makers in research and development, researchers from each institution, as well as other stakeholders.